Optimizing Multimedia Learning Objects for Learning in a Procedural-based Course - Siew, Woei Ling; May , Chan Yuen; Kee, Man Chuah (2012)
The prevalent use of multimedia learning objects in instructions particularly in e-learning platforms has spurred the interests of many studies to investigate their usability and effectiveness. It is, however, equally important to align proven instructional design principles in the design process in order to maximize learning. This study adopted Principles of Multimedia Design to guide the development of a set of learning objects for a procedural-based course, which involved 54 students for 10 weeks. The findings of the study revealed that the students showed positive acceptance of using the learning objects as the learning materials. A majority of them also reported their capability to perform the given tasks. The findings have provided valuable insights on considerations needed for the design of learning objects and confirmed that the redundancy principle within Mayer’s principles will not affect the students’ cognition largely due to the students’ language proficiency.